Phasor measurement method based on soft synchronized sampling with temporal pulse signal reference - Zhang, Jie; Tang, Chao; Liu, Chun; Wang, Hai; Junfeng, Duan; Tang, Sihao (Frontiers in Energy Research, 2023)
This paper presents a phasor measurement method based on soft synchronized, utilizing temporal pulse signals such as Pulse Per Second (PPS) from GPS and primary synchronization signals from mobile communication station. The proposed method first monitors the local oscillator using these temporal pulse signals as a reference. Subsequently, B-Spline interpolation transforms the raw sampled data influenced by the local oscillator into calibrated data with an ideal sampling rate. The calibrated data are then processed through a Recursive DFT algorithm for synchronized phasor measurement. The effectiveness of the proposed method is validated against the C37.118.1 standard, with key performance indicators such as frequency, phase, and Total Vector Error (TVE) being evaluated. The results demonstrate that the proposed software-based approach offers a simpler yet highly accurate alternative to existing hardware-based solutions, making it a practical and advanced method for synchronized phasor measurement in power grid monitoring.